Atividade biológica do feijão guandu (Cajanus cajan (L.) Millsp.) e sua possibilidade de utilização como método suplementivo do mosto cervejeiro - Lima, Felicson Leonardo Oliveira (2023)
Beer is one of the oldest alcoholic beverages of mankind, being consumed commonly in leisure time. However, some benefits of beer for human health, when ingested in moderation, have been elucidated. This drink is the result of the fermentation process of the sugars contained in the must (solution containing water, malt and hops) which, through yeast, results in the production of CO2 and ethanol. A part of the malt used for the production of beer can be replaced by other sources of carbohydrates, which are qualified as brewing adjuncts. Brewing adjuncts can be added to the beverage to meet different interests, among which are the reduction of production costs, incentive to regional agriculture, in addition to obtaining specific sensory characteristics. Pigeon pea (Cajanus cajan (L.) Millsp.) is a legume of the Fabaceae family, commonly cultivated in Northeast Brazil and in other countries with a tropical climate, being used in food for humans and other animals, in nitrogen fertilization and in traditional medicine, as it contains several bioactive compounds. Given the above and knowing the biological potential of Cajanus cajan, the present study aimed to describe the main biological activities of pigeonpea and some of its therapeutic applications, in addition to suggesting the possibility of its use as a brewing adjunct. This is a systematic review, carried out using PRISMA, consulting the PubMed, SciELO and Google Scholar databases, using materials published between 2010 and 2023. It is concluded that through the chemical and bioactive composition of pigeon pea, it can be a good alternative for use as a brewing adjunct, being able to use the drink, in addition to its economic and ecological benefits, several therapeutic effects, which requires prior laboratory evaluations for such confirmations.